2019
DOI: 10.1097/md.0000000000017186
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the stress-relieving and pharmacological actions of an ashwagandha (Withania somnifera) extract

Abstract: Background:Ashwagandha (Withania somnifera (L.) Dunal) is a herb traditionally used to reduce stress and enhance wellbeing. The aim of this study was to investigate its anxiolytic effects on adults with self-reported high stress and to examine potential mechanisms associated with its therapeutic effects.Methods:In this 60-day, randomized, double-blind, placebo-controlled study the stress-relieving and pharmacological activity of an ashwagandha extract was investigated in stressed, healthy adults. Sixty adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 33 publications
3
89
0
2
Order By: Relevance
“…27,352 Primarily, adaptogens have potential benefits in cases of behavior-related disorders, mental illness, stressinduced fatigue ( Figure 5), and cognitive function. 11,14,15,26,27,48,74,75,216,275,350,[353][354][355][356][357][358][359][360][361][362][363][364][365][366][367] In a number of clinical studies, the beneficial effects of adaptogens have been demonstrated on healthy subjects in stress conditions. 26,27,48,74,75,324,353,356,357,359,362 This is especially true of the mental and physical performance of fatigue and mental strain.…”
Section: Current and Prospective Use Of Adaptogens In Stress-inducementioning
confidence: 99%
“…27,352 Primarily, adaptogens have potential benefits in cases of behavior-related disorders, mental illness, stressinduced fatigue ( Figure 5), and cognitive function. 11,14,15,26,27,48,74,75,216,275,350,[353][354][355][356][357][358][359][360][361][362][363][364][365][366][367] In a number of clinical studies, the beneficial effects of adaptogens have been demonstrated on healthy subjects in stress conditions. 26,27,48,74,75,324,353,356,357,359,362 This is especially true of the mental and physical performance of fatigue and mental strain.…”
Section: Current and Prospective Use Of Adaptogens In Stress-inducementioning
confidence: 99%
“…Though patients take natural products and herbs to enhance their quality of life and for symptomatic management, there is little documented benefit of these products [ 122 , 123 ]. Since cancer is an inflammatory state resulting in oxidative stress with increased production of pro-inflammatory cytokines, reactive oxygen species, cyclooxygenase (COX-2), nuclear factor κB (NFκB), some of the herbal products like curcumin, Ashwagandha ( Withania somnifera ) exert immunomodulatory activity by interacting with these key mediators and exert antitumor effects [ 127 , 128 ]. A randomized clinical trial in subjects with history of chronic perceived stress using high concentration full-spectrum Ashwagandha root extract showed decrease in serum cortisol and improved resistance towards perceived stress and improved self-assessed quality of life [ 129 ].…”
Section: Natural Productsmentioning
confidence: 99%
“…Indeed, we show that the DHEA to CT ratio was significantly lower in depressed mothers compared to controls; it seems that DHEA secretion was even more sensitive than CT to allostatic pressures in depressed mothers, a finding that may be of interest when developing new therapeutic strategies for chronic maternal depression (9,12). There is some evidence that the beneficial effects of these agents are mediated by the regulation of the HPA axis (48). Depressed mothers tend to respond less sensitively to their infants' signals (49), which in turn may affect the infants' ability to regulate stress and negative emotions (38) and engage in social interactions (50).…”
Section: Discussionmentioning
confidence: 70%